Hyper ledger fabric induced supershop supply chain management model for securing product authenticity - Hossain, Md Solaiman; Faham, Nafid; Chowdhury, Sakib Hassan; Rahman, Adel; Mubin, Mohammed Fazle (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.